Rising methane emissions from northern wetlands associated with sea ice decline - Parmentier, F.J.W.; Zhang, W.; Mi, Y.; Zhu, X.; van Huissteden, J.; Hayes, D.J.; Zhuang, Q.; Christensen, T.R.; David McGuire, A. (Geophysical Research Letters, 2015)
The Arctic is rapidly transitioning toward a seasonal sea ice-free state, perhaps one of the most apparent examples of climate change in the world. This dramatic change has numerous consequences, including a large increase in air temperatures, which in turn may affect terrestrial methane emissions. Nonetheless, terrestrial and marine environments are seldom jointly analyzed. By comparing satellite observations of Arctic sea ice concentrations to methane emissions simulated by three process-based biogeochemical models, this study shows that rising wetland methane emissions are associated with sea ice retreat. Our analyses indicate that simulated high-latitude emissions for 2005-2010 were, on average, 1.7 Tg CH